Aberraciones cromosomales en bulbos de cebolla Allium cepa inducidas por moléculas híbridas 4-aminoquinolínicas - Restrepo, Ricardo; Facultad de Química Ambiental, Universidad Santo Tomás - USTA, Bucaramanga, Colombia. (2012)
To study the toxicological properties of three hybrid compounds, quinoline-thiazolidinone (FR-72 and FR-121) and acridin-epoxyisoindolindione (FR- 154), applying named compounds to the test of the roots of Allium cepa onion bulbs. Materials and methods. Molecules FR-72, FR-121 and FR-154 were synthesized de novo according to described synthetic protocols. Clean and healthy bulbs of Allium cepa (2n = 16), previously immersed in distilled water, were dried with paper towels and placed directly into test tubes filled with the test substance. The experiments were carried out at room temperature 20 ± 2°C and were kept in darkness. The period of exposure of bulbs was 120 hours; the roots used for the genotoxicity evaluation were on average of 2 to 2.5 cm in length. The evaluation of the effect of the three quinolinic molecules on the growth of onion roots of Allium cepa bulbs was achieved using different concentrations of the three growth parameters (EC50, IM, ACs) The evaluated substances performed aneugenic actions, operating at cellular and molecular structure level and preventing the fixing of mitotic spindle fibers, causing the movement of chromosomes in the anaphase or loss of chromosomes, even inducing apoptosis by exceeding the homeostatic capacity of the cell. Conclusions. The preliminary analysis indicated that molecule FR-121 at 10-6 M concentration and molecule FR-154 at 10-3 M concentration, proved to be potent phytotoxic agents causing various claustogenic and aneugenic aberrations.